Florite® R as a model for incorporation of essential oils as active substances into a solid dosage pharmaceutical form - Jončić Savić, Katarina; Pavlović, Bojan; Beara, Ivana; Simin, Nataša; Lesjak, Marija (Archives of Pharmacy, 2022)
Application of essential oils in modern medicine has a limited use due to its specific physico-chemical properties which can make them extremely unsuitable for the formulation of stable pharmaceutical forms. The aim of this study was to develop robust hard capsules formulation with natural essential oil mixture (HerbELICO®) which has confirmed anti-Helycobacter pylori activity. Unique Calcium Silicate (Florite® R, Tomita Pharmaceutical Co., Ltd.) with its high liquid adsorption ability was used for preparing Unique HerbELICO® powder where HerbELICO® mixture of essential oils was loaded on Florite® R by mixing in the range from 70 to 80 % (w/w). The factorial design of experiments was applied to systematically optimise the physical characteristics of capsules containing Unique HerbELICO® Powder and filler in different ratio The prepared Unique HerbELICO® Powders were evaluated for their flowability, bulk and tapped density and angle of response, and based on these parameters the optimum formulation was selected. HerbELICO® solid capsules were evaluated for their weight variation. The experimental results have shown that the content of up to 30% (w/w) of Unique HerbELICO® Powder per capsule still provided physico-chemical properties in the acceptable limits. The present study promotes HerbELICO® solid capsules formulation as a model of the successful incorporation of essential oils into a solid dosage form. The advantage of the developed capsules is possibility to use essential oils in robust pharmaceutical form suitable for massive production, and convenient for oral use.